Perceptions of the effectiveness of health care for probationers. Issue 2 (2nd April 2020) - Sirdifield, Coral; Marples, Rebecca; Denney, David; Brooker, Charlie
Abstract : Purpose: This study aims to investigate the views of commissioners, providers and criminal justice staff on how effective current health-care provision is at meeting the health needs of people on probation. Understanding perceptions of what constitutes effective provision, where barriers are encountered and where improvements could be made is an important step towards improving access to care for this hard-to-reach group. Design/methodology/approach: The research was part of a wider study. This paper focusses on findings from case studies conducted via semi-structured telephone interviews with 24 stakeholders in a purposive sample from six geographical areas of England. Interviews were conducted by researchers from a variety of backgrounds and an individual with lived experience of the criminal justice system. Data were analysed using thematic analysis. Findings: Participants provided examples of effective health-care provision, which largely involved multi-agency partnership working. It was apparent that there are many barriers to providing appropriate health-care provision to people on probation, which are underpinned by the complexity of this population's health-care needs, the complexity of the health-care landscape and problematic commissioning processes. Practical implications: Improvements are needed to provide appropriate and accessible health care that meets the needs of people on probation, thereby reducing health inequalities. These include shared targets, improved funding, clearer pathways into care and giving probation a voice in commissioning. Originality/value: To the best of authors' knowledge, this is the first study of commissioner, provider and criminal justice staffs' views on the effectiveness of current health-care provision at meeting the health needs of people on probation.